A ubiquitous chromatin opening element prevents transgene silencing in pluripotent stem cells and their differentiated progeny123. (25th February 2013) - Pfaff, Nils; Lachmann, Nico; Ackermann, Mania; Kohlscheen, Saskia; Brendel, Christian; Maetzig, Tobias; Niemann, Heiner; Antoniou, Michael N.; Grez, Manuel; Schambach, Axel; Cantz, Tobias; Moritz, Thomas
Abstract Methylation‐induced gene silencing represents a major obstacle to efficient transgene expression in pluripotent cells and thereof derived tissues. As ubiquitous chromatin opening elements (UCOE) have been shown to prevent transgene silencing in cell lines and primary hematopoietic cells, we hypothesized a similar activity in pluripotent cells. This concept was investigated in the context of cytidine deaminase (CDD) gene transfer, an approach to render hematopoietic cells resistant to the chemotherapeutic agent Ara‐C. When murine induced pluripotent stem cells (iPSC)/embryonic stem cells (ESCs) were transduced with self‐inactivating lentiviral vectors using housekeeping (truncated elongation factor 1α; EFS) or viral (spleen focus‐forming virus; SFFV) promoters, incorporation of an heterogeneous nuclear ribonucleoproteins A2 B1/chromobox protein homolog 3 locus‐derived UCOE (A2UCOE) significantly increased transgene expression and Ara‐C resistance and effectively prevented silencing of the SFFV‐promoter. The EFS promoter showed relatively stable transgene expression in naïve iPSCs, but rapid transgene silencing was observed upon hematopoietic differentiation. When combined with the A2UCOE, however, the EFS promoter yielded stable transgene expression in 73% ± 6% of CD41+ hematopoietic progeny, markedly increased CDD expression levels, and significantly enhanced Ara‐C resistance in clonogenic cells. Bisulfite sequencing revealed protection from differentiation‐induced promoter CpG methylation to be associated with these effects. Similar transgene promoting activities of the A2UCOE were observed during murine neurogenic differentiation, in naïve human pluripotent cells, and during nondirected multilineage differentiation of these cells. Thus, our data provide strong evidence that UCOEs can efficiently prevent transgene silencing in iPS/ESCs and their differentiated progeny and thereby introduce a generalized concept to circumvent differentiation‐induced transgene silencing during the generation of advanced iPSC/ESC‐based gene and cell therapy products. STEM CELLS2013;31:488–499